Beam-steering metasurfaces assisted coherent optical wireless multichannel communication system - Tao Jin; You Quan; Yang Chao; Li Zile; Deng Liangui; Wu Mian; Luo Ming; Wu Lin; Li Chao; Liu Zichen; He Zhixue; Xiao Xi; et al. (Nanophotonics)
The metasurface based beam-steering devices with the advantages of large steering angles, arbitrary channels and ultra-compactness have played an important role for data allocation and exchange in the optical wireless communication. However, the current metasurface based optical wireless communication systems are mainly on intensity modulation and direct detection (IM/DD), which shows a relative lower transmission capacity, lower received optical signal-to-noise ratio (OSNR) and complexity of system. In this study, a bidirectional multichannel optical wireless system enabled by a polarization independent metasurface with coherent modulation and reception is designed and experimentally demonstrated, which exhibits exclusive 100 Gbps coherent optical signals to multiusers with their own wavelengths, 2 m free space distance and field of view of 20° × 20°. In addition, the proposed system can support optical broadcasting system with capacity of 900 Gbps. The demonstrated metasurface assisted optical wireless communication system merges the optical coherent communication techniques and emerging concept of metasurface, which reduces the complexity and cost of the system while contributing a high transmission capacity, opening a new avenue for high performance optical wireless communications.